In Vitro Study for Yttrium addition on titanium - 15 Molybdenum after Immersion in Simulated Body Fluid (Journal of Pharmaceutical Negative Results, 2022)
Multiple attempts are made to develop bioactive alloy for the construction of the implant to enhance osseointegration and support implant functions. The titanium – 15 Molybdenum alloy with and without the addition of Yttrium makes an organic-inorganic hybrid composite that has the ability to make a network with or without covalent bonds between components. In this study the immersion of Titanium – 15 Molybdenum disc and titanium – 15 Molybdenum- 1.5 Yttrium in simulated body fluid.The unique biomaterial multi-component Ti-Mo-1.5Y alloys were created as a way to improve the bioactivity characteristics and lessen the toxicity of biomaterials for implants in order to create new biomaterials for implant applications. The purpose of this study is to look at how adding yttrium (Y) changes the alloy's bioactivity. Through the use of powder metallurgy, Ti-Mo-1.5Y alloys are created. Atmospheric pressure high-purity argon gas is used to sinter the metals. samples were immersed in SBF in closed containers and placed in incubators at a temperature of 370 C for 30 days. Analysis of the surface includes thickness measurement, X-ray diffraction (XRD), and an optical microscope. The results of showed an increase in the thickness of (HA) with the addition of yttrium after immersion in SBF compared with thickness before the addition of yttrium. The results of XRD showed the appearance of new peaks of HA, and showed there are additional accumulates of HA granules when adding yttrium content after immersion in SBF.